Injury, illumination and freedom: thinking about the afterlives of apartheid through the family albums of District Six, Cape Town - O’Connell, Siona (International journal of transitional justice, 2015)
This reflexive article enters a conversation about freedom and justice through the family photographs found in the homes of forcibly removed ex-residents of District Six, Cape Town, in an attempt to think about ways of living after apartheid. It engages with the challenges of restitutive justice against the backdrop of South Africa’s Truth and Reconciliation Commission, addressing as well questions of trauma, memory and freedom in the aftermath of oppression. The article examines the complexities of the land claims process of District Six and, in doing so, places three seemingly distinct literatures in the same methodological frame: that of photography, that of memory and that of justice and freedom. In the conflict over land that has characterized District Six, what is clear is that the problem cannot simply be undone with financial remuneration, that land itself is imbued with a meaning that is not reducible to monetary terms alone. Unless we recognize the multidimensionality of home, oppression and injustice, any attempts to engage in restitution are destined to fail. This article uses an apparently innocuous object - the family photographs of the oppressed - to initiate interdisciplinary dialogue on what justice and freedom may yet mean in postapartheid South Africa.